The CX-DZ-II intelligent electronic stimulator for neck pain caused by cervical spondylosis: A two-center, randomized, controlled, and non-inferiority trial - Chen, Liping; Li, Dehua; Xu, Jing; Liang, Hao; Zhang, Ya; Ren, Yulan; Liang, Fanrong (Frontiers in Neuroscience, 2022)
Background: Electroacupuncture (EA) has been commonly used for the management of neck pain caused by cervical spondylosis (NPCS), however, current electrical instruments have limitations on intelligence, digitalization and visualization. The intelligent electronic stimulator (CX-DZ-II) is a digital device with an evidence-based diagnosis and treatment system. This study aimed to investigate the efficacy and safety of the CX-DZ-II intelligent EA instrument for NPCS. Methods:164 patients with NPCS (mean age [SD], 49.48[13.47] years) were randomly assigned to receive 8-sessions (over 2 weeks) EA of the intelligent electronic stimulator (CX-DZ-II) or regular electronic stimulator (SDZ-II). The primary outcome was the change of VAS from baseline to week2 treatment. Secondary outcomes included mean scores of VAS after each treatment in week1, responder rate, drug-usage rate of non-steroidal antipyretic analgesic (NSAAs), the occurrence rate of adverse events, proportions of apparatus with defect during treatment, and excellent rate of apparatus. Results: The intelligent electronic stimulator(CX-DZ-II) was noninferior to regular electronic stimulator (SDZ-II) for changes from baseline in VAS (3.36 vs 3.23, with a difference of 0.17[95%confidence interval,-0.36 to 0.69], P＜0.025 for noninferiority). No between-group differences were found in outcomes of VAS in week1, overall responders and drug-usage rate of NSAAs. The defect rate and excellent rate of instrument were similar in CX-DZ-II and SDZ-II groups. Adverse events occurred in 9(10.84%) patients in the CX-DZ-II group and 4(5.00%) in the SDZ-II group. Conclusions: The intelligent electronic stimulator (CX-DZ-II) was noninferior to regular electronic stimulator (SDZ-II) in relieving neck pain. The intelligent electronic stimulator (CX-DZ-II) is a promising noninferior alternative instrument for NPCS. Clinical Trial Registration: This study was registered in Clinical Trials. Gov (Trial registration No. NCT03005301) Keywords: neck pain, cervical spondylosis, electroacupuncture, electronic stimulator